Answer:
a)
The pmf of x is
x p(x)
1 0.33
3 0.11
4 0.04
6 0.38
12 0.14
b)
P(3≤X≤6)=0.53
P(X≥4)=0.56
Step-by-step explanation:
a)
We have to find pmf of x.
We know that
F(x)=P(X≤ x)
F(0)=P(X≤ 0)=P(X=0)=f(0)
F(1)=P(X≤ 1)=P(X=0)+P(X=1)=f(0)+f(1)
As, f(0)=F(0), so
f(1)=F(1)-F(0)
F(2)=P(X≤ 2)=P(X=0)+P(X=1)+P(X=2)=F(1)+f(2)
f(2)=F(2)-F(1)
So, we can say that
f(3)=F(3)-F(2)
f(4)=F(4)-F(3)
f(6)=F(6)-F(5)
f(12)=F(12)-F(11).
We are given that
F(0)=0 ,F(1)=0.33 ,F(2)=0.33 ,F(3)=0.44, F(4)=0.48, F(5)=0.48, F(6)=0.86, F(7)=0.86, F(8)=0.86, F(9)=0.86, F(10)=0.86, F(11)=0.86, F(12)=1.
We have to find f(1), f(3), f(4), f(6) and f(12).
f(1)=F(1)-F(0)=0.33-0=0.33
f(3)=F(3)-F(2)=0.44-0.33=0.11
f(4)=F(4)-F(3)=0.48-0.44=0.04
f(6)=F(6)-F(5)=0.86-0.48=0.38
f(12)=F(12)-F(11)=1-0.86=0.14
The pmf of x is
x p(x)
1 0.33
3 0.11
4 0.04
6 0.38
12 0.14
b)
P(3≤X≤6)=?
We know that P(a<X≤b)=F(b)-F(a)
P(3≤X≤6)=P(2<X≤6)=F(6)-F(2)=0.86-0.33=0.53
P(3≤X≤6)=0.53
P(X≥4)=?
P(X≥4)=1-P(X<4)=1-P(X≤3)=1-F(3)=1-0.44=0.56
P(X≥4)=0.56